Exploring transformative travel experiences: The case of Turkish travelers - Gurel Cetin; Tugba Pala (Tourism & Management Studies)
Transformative tourism experiences result in long term changes on attitudes and behavior. Although research on transformative tourism has flourished in recent years, there is still a limited number of studies that investigate the travellers’ experiences to examine the impact of travel on one’s attitudes and behaviors. This exploratory study seeks to identify factors affecting transformative travel experiences to emerge. A typology of sustained travel transformations is also offered based on result of a qualitative case study conducted on Turkish travelers. As a result of thematic content analysis of in-depth interviews with 30 travelers, main themes affecting travel transformations emerged as tripograhic, personal and destination based determinants, whereas the types of transformations were classified under behavioral, attitudinal and personality changes. If tourist transformations could be understood better, this might result in better promotion of travel as a leisure activity not just at the individual level but at the policy level. Destinations, tour operators and other hospitality organizations would position their product in a potentially more transformative way if they know the causes and outcomes of travel related transformations.